A Survey on E- Commerce Online Shopping - Palanisamy, Ramaraj (Recent Research Reviews Journal, 2022)
Due to advancements in technology, networks are now necessary for the operation of our day-to-day lives. In the modern corporate world, online shopping is quite important. Online shopping has given businesses more opportunities and advantages. Through online shopping, the customer can find the product easily and compare the price of the same product among several online sites. Various e-commerce companies can provide multiple promotional offers like discounts, free delivery, cashback offers, return policy, etc. This paper explores the meaning of e-commerce and online shopping, its process, advantages, and disadvantages of online shopping in India, with a focus on features and challenges. The purpose of this study is to analyse the various applications of online shopping in India. Additionally, the paper highlights the difficulties that customers have when they decide to adopt online shopping.